Kedudukan Hukum Adat Laot dalam Sistem Hukum Nasional - Teuku Muttaqin Mansur (Universitas Syiah Kuala, 2010)
ABSTRACT: The customary law of the sea for the furthere mentioned as hukum adat la’ot is the customary law conducted by the Aceh’s fisherman community to provide some prosedures on catching fish and the fisherman community life. In the coastal area. In the hukum adat la’ot is contained regarding the procedures of catching the fish (meupayang) at the sea and also contains the mechanism dispute settlement if occuring customary dispute among fisherman. Hukum adat la’ot has existed since 400 years ago. Nowadays, hukum adat la’ot has got the strong position in the Indonesia legal sistem as stated in several hyrarchy of Indonesia’s laws, the last as stated in article 162 (2), abjad (e) the law Number 11 year 2006 regarding The governing of Aceh and it’s proceeding in regional regulation (Qanun) Number 9regardingthe supervising of Adat La’ot and the the customary behavior and Qanun Aceh Number 10 regarding the Customary board. The Structure of Hukum Adat Laot in the National legal system